Natural Weathering Effects on Mechanical and Thermal Properties of Bamboo Cotton Textile Waste Reinforced Recycled Polypropylene Composites for Construction Applications - Wan Jun Arifin, Wan Ariza; Ahmad, Mazatusziha; Reazul Haq Abdul Haq, (Progress in Engineering Application and Technology, 2026)
The increasing generation of plastic and textile waste has become a serious environmental issue and has encouraged the development of more sustainable materials. In this study, bamboo cotton textile waste (BCTW) was used as a natural reinforcement in recycled polypropylene (rPP) composites to study the effects of natural weathering on mechanical and thermal properties. The composites were prepared with different BCTW loadings using an internal mixing and compression moulding process, with maleic anhydride grafted polypropylene (MAPP) added as compatibilizer. Natural weathering exposure carried out under outdoor conditions. Prior to weathering, the BCTW were characterized using Fourier Transform Infrared Spectroscopy (FTIR) and Field emission scanning electron microscopy (FESEM) followed by composites testing using differential scanning calorimetric (DSC) to evaluate the initial chemical, morphological and thermal properties. The effects of natural weathering were analyzed based on changes observed in tensile and thermogravimetric (TGA) results. The results show that the addition of BCTW increased the stiffness of the composites while tensile strength showed better performance at moderate fiber contents. Thermal analysis indicated a slight reduction in thermal stability after weathering exposure. Among all formulations, the composite with 15 wt% BCTW shows the most balanced overall performance after weathering. Overall, the findings suggest that bamboo cotton textile waste reinforced recycled polypropylene composites have good potential as sustainable materials for outdoor applications.